2009
DOI: 10.1103/physrevb.79.212509
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a reentrant superconducting state inEuFe2As2under pressure

Abstract: We studied the temperature-pressure phase diagram of EuFe 2 As 2 by electrical resistivity measurements. The spin-density-wave transition at T 0 associated with the FeAs-layers is continuously suppressed with increasing pressure, while the antiferromagnetic ordering temperature of the Eu 2+ moments seems to be nearly pressure independent up to 2.6 GPa. Above 2 GPa a sharp drop of the resistivity, ͑T͒, indicates the onset of superconductivity at T c Ϸ 29.5 K. Surprisingly, on further reducing the temperature, ͑… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(191 citation statements)
references
References 31 publications
(21 reference statements)
17
170
4
Order By: Relevance
“…Very recently, Jeevan et al discovered hightemperature superconductivity in EuFe 2 As 2 [18] and now, we report the superconductivity of Eu 0.7 Na 0.3 Fe 2 As 2 . It clearly demonstrates that EuFe 2 As 2 is a new member of the ThCr 2 Si 2 -type Fe-As superconductor family [22], and offers the opportunity to study the mechanism of new iron-based superconductors.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Jeevan et al discovered hightemperature superconductivity in EuFe 2 As 2 [18] and now, we report the superconductivity of Eu 0.7 Na 0.3 Fe 2 As 2 . It clearly demonstrates that EuFe 2 As 2 is a new member of the ThCr 2 Si 2 -type Fe-As superconductor family [22], and offers the opportunity to study the mechanism of new iron-based superconductors.…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that under pressure the 122 parents themselves become superconducting [7][8][9] . This led to the finding that even substitutions of isovalent elements, for example, P 10 for As or Ru 11 , Ir 12 , Pd 13 or Rh 13 for Fe, induce superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…56 The SC state can be achieved either under pressure 57,58 or by appropriate charge carrier doping 59 of the parent compounds, leading to a suppression of the SDW state. Our first task was to check whether magnetism is present in the samples.…”
Section: A Magnetization and Specific Heat Capacity Experimentsmentioning
confidence: 99%